Multi-correlation between nematode communities and environmental variables in mangrove-shrimp ponds, Ca Mau Province, Southern Vietnam - Thai, Tran Thanh; Yen, Nguyen Thi My; Son, Hoang Nghia; Quang, Ngo Xuan (Academia Journal of Biology, 2020)
Multi-correlation between bio-indices of nematode communities and ecological parameters in mangrove-shrimp farming ponds in Tam Giang commune, Nam Can District, Ca Mau Province, Vietnam were investigated. In which, diversities of nematode communities and several environmental variables in eight ponds were considered to process. Our findings underlined the high diversity of nematode communities in mangrove-shrimp farming ponds compared to other mangrove habitats. Nematode diversities provided more oppotunity in natural food for shrimp. Single correlation analyses showed that the species richness index correlated significantly to three variables (salinity, total organic carbon, and total nitrogen), the Margalef diversity index correlated to two variables (salinity, total organic carbon), and the expected number of species for 50 individuals index correlated with one variable (salinity). Results of multi-correlation analyses between the nematode bio-indices and the environmental variables were completely different from those of single-correlation analyses. In multi-correlation analyses, the species richness and the Margalef diversity index correlated to two variables (salinity, total organic carbon), Pielou’s evenness index and Hill indices correlated with dissolved oxygen, also the Hurlbert index correlated to total organic carbon. Hence, it is necessary to pay attention to the impact of complex interactions between the multi-environmental variables and nematode communities. This research aims to explain the differences between single- and multi-correlation for evaluation of the effects of environmental factors on nematodes as well as aquatic organisms.